Effect of metformin therapy on 2-h post-glucose insulin levels in patients of polycystic ovarian syndrome - Pikee Saxena (Journal of Human Reproductive Sciences, 2010)
Aims : To evaluate if 2-h post glucose insulin level is an effective tool to monitor insulin resistance in response to metformin therapy, in infertile women with polycystic ovarian syndrome (PCOS). Settings and Design : This prospective observational study was carried out in a tertiary care infertility clinic. Materials and Methods : 40 women with PCOS were categorized as having insulin resistance if fasting or 2-h post glucose insulin levels were >25 or >41μU/ml respectively. Post glucose insulin was compared before and after six months of metformin therapy along with other clinical, hormonal and metabolic parameters by using McNemar and the Student′s t-test. Results : Fasting insulin was elevated in 4 (10%) and post-load insulin in 34 (85%) patients; after metformin therapy respective values were 2 (5%) and 16 (40%). Metformin therapy reduced post glucose insulin levels (P<0.001), improved the regularity of periods (P<0.001) and resulted in reduction of LH levels (P<0.001), total testosterone (P<0.001) and mean Body mass index (BMI) (P=0.047). Metformin therapy did not alter waist-hip ratio and fasting insulin levels. Conclusion : 2-h post glucose insulin level is an effective tool to monitor insulin resistance in PCOS patients and improves significantly after metformin therapy, similar to improvements observed in clinical, hormonal and metabolic parameters.